Professional Crystal Reports for Visual Studio .NET - McAmis, David (Wiley, 2004)
What is this book about? The addition of Crystal Reports 9.0 to Visual Studio .NET 2003 offers developers a reporting tool that allows you to turn almost any data into interactive, dynamic content through portals, wireless devices, and Microsoft Office documents. This code-intensive guide takes you step by step through developing reports and incorporating them into applications. First, you gain a thorough understanding of how this version of Crystal Reports differs from previous versions and how it fits into the .NET platform. Then you begin creating reports and learn how to integrate t.